Trapezius muscle branch of the spinal accessory nerve without penetrating the sternocleidomastoid muscle as a pitfall in neck dissection: prevalence in a Japanese institution and a protocol for the prevention of iatrogenic injury. (2nd August 2021) - Sakamoto, Koji; Ozawa, Hiroyuki; Shimanuki, Marie; Kida, Amina; Kitama, Tsubasa; Iwabu, Kaho; Nakaishi, Masashi; Sakanushi, Atsuko; Matsunobu, Takeshi; Okubo, Kimihiro; Sato, Yoichiro; Shinden, Seiichi; et al.
Abstract: Background: The spinal accessory nerve (SAN) has several anatomical variations, which may be a pitfall in neck dissection (ND). These include the trapezius muscle branch (TB), which stems from the common trunk before entering the sternocleidomastoid muscle (SCM). Aims/Objectives: To investigate the prevalence of this variation and suggest a protocol for preventing unexpected injury of the TB in ND. Materials and methods: We conducted a retrospective cohort study for 93 patients who had undergone neck dissection (117 sides) without resection of the SCM nor SAN. We recorded the division of the TB after and before penetration of the SCM by the common trunk (penetrating type TB [PTB]) and non-penetrating type TB [NPTB], respectively). Results: Among NDs, PTB and NPTB were observed in 61 (52%) and 56 (48%) sides, respectively. In the subgroup of 24 cases with bilateral ND, PTB/PTB, NPTB/NPTB, and NPTB/PTB were observed in eight (33%), nine (38%), and seven (29%) cases, respectively. The prevalence of PTB/NPTB did not differ according to age, sex, or laterality. Conclusions and significance: NPTB is a common anatomical variation. The presence or absence of a branch from the common trunk must be initially checked to avoid unexpected damage to the TB.